PREFACE - To the book by Nono Sumampouw, Menjadi Manado: Torang Samua Basudara, Sabla Aer, dan Pembentukan Identitas Sosial - Schouten, Maria Johanna Christina (2015)
Preface to an anthropological study about the city of Manado (Indonesia). Attention is paid to its geostrategic location and the diversity of its population, in a historical perspective. Includes reflections on anthropological practices and analysis.